THE INFLUENCE OF DIGITAL COMMUNICATION COMPETENCE ON STUDENT MOTIVATION - Pratiwi, Shilvia Rahma; Malik, A.; Hadi, T.S (Lektur: Jurnal Ilmu Komunikasi, 2025)
Digital transformation has significantly impacted various aspects of life, particularly in communication. In today's digital era, many universities have adopted digital learning through Learning Management System (LMS) platforms, shifting from conventional communication methods to digital ones. As this evolution unfolds, digital communication competence has become essential for students to communicate effectively, even within digital media like LMS. This research analyzes and assesses how digital communication competence influences students' learning motivation. The study employs a mixed-methods approach, utilizing an explanatory research design with a sequential explanatory framework. Data sources were gathered through observations, interviews, and the distribution of questionnaires. Interview participants were selected through purposive sampling. Quantitative data analysis was conducted using SmartPLS 3.0, supplemented by qualitative analysis. Data credibility was tested through source triangulation. The findings reveal that digital communication competence significantly impacts students' learning motivation, with an effect size of 69.7%. Additionally, the results support Computer-Mediated Communication (CMC) theory, which posits that digitalization can create new communication patterns facilitated by digital media. Recommendations include encouraging students to enhance their digital communication skills, while universities are urged to improve their LMS to achieve better overall performance continuously.